Molecular basis of avascular necrosis of the head of the femur: Facts to ponder - Pasuk Mahakkanukrauh (2018)
© 2017 Japan Health Sciences University & Japan International Cultural Exchange Foundation. Background: Avascular necrosis of the head of the femur is a serious event which occurs following any trauma. There is profuse blood loss due to rupture of arteries supplying the head of the femur. There may be possible association of any gene with avascular necrosis of the head of the femur. Design: A short narrative review for genes involved in the avascular necrosis of femur. Methods: A thorough search of literature was done to scrutinize various published papers related to avascular necrosis of head of femur and the genes involved were noted. Results: The retrieved results showed the involvement of various genes in avascular necrosis of the head of the femur. Genes related to Alpha-2 macroglobulin (A2M), basic fibroblast growth factor (bFGF), Sterol regulatory element binding factor, Osteoprotegerin (OPG), Receptor Activator of Nuclear Factor kappa-B (RANK) and RANK ligand (RANKL), Bone morphogenetic proteins, COL2A1 mutations and Factor V Leiden were found to influence avascular necrosis of the head of the femur. Conclusion: Knowledge of the genes involved in avascular necrosis of the head of femur may be important for academic and therapeutic purpose. The knowledge of the genes linked to such avascular necrosis could also form the basis of future stem cell treatment.